Pengaruh Daya Tarik Pesan Iklan Layanan Masyarakat di Youtube dan Tingkat Pengetahuan Masyarakat Terhadap Keputusan Menggunakan Vaksin Measles dan Rubella (Mr) pada Anak (Studi Eksplanatif pada Subscribe Iklan Layanan Masyarakat Vaksin Measles dan Ru: Pengaruh Daya Tarik Pesan Iklan Layanan Masyarakat di Youtube dan Tingkat Pengetahuan Masyarakat Terhadap Keputusan Menggunakan Vaksin Measles dan Rubella (Mr) pada Anak (Studi Eksplanatif pada Subscribe Iklan Layanan Masyarakat Vaksin Measles dan Rubella Versi Panjang) - Ilona Vicenovie Oisina; Ivonne Ruth Vitamaya Oishi (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Social media is the target of advertisers to advertise various products and services. Similarly, public service advertisements use social media to advertise. The selected social media varies depending on needs. Public service advertisements about MR vaccines are available on various social media, one of which is on Youtube, with many versions. In this study took public service advertisements about the long version of the MR vaccine. It is expected that public service advertisements can provide knowledge for users to know that MR vaccines are important for children’s development, and not contrary to any religion. This research uses the theory of Computer Mediated Communication. The paradigm used positivism with quantitative approaches, the nature of explanatory research and survey research methods. The population is to subscribe to 2146 public service advertisements as of January 2018 with a sample of 96 respondents taken using purposive sampling. The results obtained from the relationship of the attractiveness of public service advertisements and the level of knowledge with use decisions are 0.494. F count test> F table is 15,768> 3,099, it can be concluded that there is a simultan eous influence of the attraction of MR vaccine public service ads and the level of knowledge on the decision to use MR vaccine.